Towards a Transnational Political History of North America: The View from Canada - Robert MacDougall (Nuevo mundo - Mundos Nuevos, 2010)
This article voices three “heresies” against the nationalist, centralist, and anti-American biases of traditional political history in English Canada, in hopes of opening the way to a more transnational understanding of the Canadian and North American past: Canada’s history is an American history, in constant dialogue with the history of the United States; Canada’s Confederation in 1867 was not an an act of national unification, but a compact between autonomous regions, as French-Canadian historians have long maintained; Canadian federalism is not failing, and in fact represents a remarkably flexible and successful form of government, well suited to Canada’s geography and cultural diversity. Only by rejecting the “narcissism of small differences” and the “solipsism of American exceptionalism” can we foster a truly transnational North American history.